Focus on leveling the hidden: managing impacted maxillary canines - Orlando Motohiro TANAKA; André WEISSHEIMER; Matheus Melo PITHON; Gil Guilherme GASPARELLO; Eustáquio Afonso ARAÚJO (Dental Press Editora, 2024)
ABSTRACT Introduction: The long pathway that the canines take as they emerge into the maxillary arch makes them vulnerable to disruption during their natural emergence time. The process of planning treatment for impacted maxillary canine (IMC) presents significant challenges, underscoring the need for careful consideration and expertise. Objective: The aim of this article was to shed light on these complexities by discussing clinical case studies involving IMC, providing insights into the intricacies of their management. Conclusions: The management of IMC within orthodontics presents a multifaceted challenge that include the necessity for precise diagnostic processes, prudent use of cone beam computed tomography (CBCT), the strategic selection between open and closed exposure techniques, a in-depth understanding of the specific orthodontic biomechanics involved, and a keen awareness of potential adverse outcomes such as ankylosis, prolonged treatment times, root resorption, and additional complications.